The quality characteristics of sausage prepared from different ratios of fish and duck meat - Bozhko, Nataliia; Tyshchenko, Vasyl; Pasichnyi, Vasyl; Shubina, Yevgenia; Kyselov, Oleksandr; Marynin, Andriy; Strashynskyi, Igor (My University, 2021)
The article aims to determine the effect of combining duck meat (Anas platyrhynchos) and freshwater fish (Hypophthalmichthys molitrix) on the quality (nutritional value, functional and technological properties, sensory attributes) of meat-containing semi-smoked sausages. The optimal version of the recipe with the highest quality indicators of semismoked meat sausages with duck meat and freshwater aquaculture was determined. It was found that the protein content of meat-containing, semi-smoked sausages with different ratios of duck and fish meat was 17.90% – 21.34% higher than that of the analog. A sample containing 50% duck and 30% fish has an ideal protein: fat ratio of 1:1. The following high functional properties of model minced experimental semi-smoked sausages were established: up to 72.75% moisture, water binding capacity of up to 71.47%, and water holding capacity of up to 60.60%. A comparative analysis of the rheological properties of minced meat showed that increasing the proportion of duck meat in minced meat modelling systems improves the strength of the system and increases shear stress. The addition of fish raw materials improves the elasticity of meatcontaining systems. The optimal ratio of duck and fish is 50:30 for plastic and easily minced mince system. Combining duck meat with raw fish increases the stability of the emulsion to 74.8%. Analysis of the sensory parameters of the experimental sausages confirmed that the best ratio of duck to freshwater fish is 50:30. Метою статті є визначення ефекту поєднання м’яса качки (Anas platyrhynchos) та прісноводної риби. (Hypophthalmichthys molitrix) за якістю (харчова цінність, функціональні та технологічні властивості, сенсорні ознаки) м'ясомісних напівкопчених ковбас. Оптимальний варіант рецептури з найвищими якісними показниками напівкопченого м'ясні ковбаси з м'ясом качки та прісноводної аквакультури. Встановлено, що вміст білка в м’ясомістких, напівкопчених ковбас з різним співвідношенням м’яса качки та риби на 17,90% – 21,34% більше, ніж аналога. Зразок, що містить 50% качки та 30% риби, має ідеальне співвідношення білка: жиру 1:1. Наступний високий встановлено функціональні властивості модельного фаршу дослідних напівкопчених ковбас: до 72,75% вологи, води зв'язуюча здатність до 71,47%, водоутримуюча здатність до 60,60%. Порівняльний реологічний аналіз властивості фаршу показали, що збільшення частки качиного м'яса в системах моделювання фаршу покращується міцність системи і збільшує напругу зсуву. Додавання рибної сировини покращує пружність м'ясного вмісту системи. Оптимальне співвідношення качки і риби - 50:30 для системи пластичного і легко подрібнюваного фаршу. Комбінування м'ясо качки з сирою рибою підвищує стійкість емульсії до 74,8%. Аналіз сенсорних параметрів експериментальні сосиски підтвердили, що найкраще співвідношення качки і прісноводної риби – 50:30.
Keywords: кафедра технології м’яса і м’ясних продуктів; duck meat; риба прісноводна; м'ясо качки; semi-smoked sausage; ковбаса напівкопчена